Global climate change and peatland carbon balance: an overview - Wieder,R.K.; Yavitt,J.B.; Novak,M. (Journal of the Czech Geological Society, 1994)
Considerable quantities of carbon have been removed from the atmosphere and stored as peat since the most recent glaciation. The conceptual framework for understanding peat accumulation and carbon balance in peatlands has long been established, yet substantial gaps exist in our understanding of processes related to carbon balance in peatlands and of the source/sink relationships for CH4 and CO2 between peatlands and the atmosphere. Few estimates of net primary production for peatland ecosystems exist; belowground production and its contribution to peatland carbon balance have been largely ignored. The extent to which site-specific field measurements of CH4 and CO2 emissions from peatlands can be generalized to broader geographic areas remains uncertain. Relatively little work has focused on the microbially mediated mechanisms of CH4 and CO2, production/consumption within the peat itself or on the population and community dynamics of the microorganisms responsible for carbon mineralization in peat. Such gaps in our current understanding of present-day carbon cycling in peatlands confound efforts to project how peatland ecosystem function may be altered under predicted scenarios of global climate change.